Cholinesterase Enzyme Association with Quality of Life Among Farmers in Khong Chai District, Kalasin Province, Thailand - Supasin Deeraksa; Mayuree Suwunnakhot; Khanittha Madngammuang (Jurnal Keperawatan Indonesia, 2025)
The agricultural sector in Thailand faces challenges that impact farmers' health and quality of life. This study examines the quality of life, cholinesterase enzyme levels, and factors associated with quality of life among farmers in Khong Chai District, Kalasin Province, Thailand. This cross-sectional analytical study was conducted using systematic random sampling. The respondents had a mean age of 54.97 ± 10.50 years (range 25–75 years) and comprised 75.56% females (n = 204), 24.44% males (n = 66). Data collection included demographic information, blood samples to assess cholinesterase enzyme safety levels, and responses to the World Health Organization Quality of Life Brief-Thai (WHOQOL-BREF-THAI) questionnaire. Data were analyzed using descriptive and inferential statistics. Multiple linear regression was utilized to identify factors associated with WHOQOL-BREF-THAI scores, presenting adjusted mean differences, 95% confidence intervals (95% CI), and p-values. The mean of WHOQOL-BREF-THAI score was 89.97 ± 10.34. Factors associated with higher quality of life scores included gender (male: 3.06; p = 0.032), agricultural land size of 10 Rai (1600 m2) or more (2.55; p = 0.039), frequency of cholinesterase blood testing (1 time: 3.01; never: 3.40; p = 0.039; reference: 2 times or more), and blood cholinesterase enzyme safety levels (unsafe: 1.69; p = 0.037). These findings highlight the need for interventions to reduce risk factors, particularly among farmers with unsafe cholinesterase enzyme levels, to improve the quality of life in this population.Keywords: cholinesterase enzyme safety levels, farmers, quality of life (QoL)AbstrakEnzim Kolinesterase Berhubungan dengan Kualitas Hidup Petani di Distrik Khong Chai, Provinsi Kalasin, Thailand. Sektor pertanian di Thailand menghadapi tantangan yang mempengaruhi kesehatan dan kualitas hidup petani. Penelitian ini mengeksplorasi kualitas hidup, kadar enzim kolinesterase, dan faktor-faktor yang berhubungan dengan kualitas hidup petani di Distrik Khong Chai, Provinsi Kalasin, Thailand. Kami melakukan studi analisis cross-sectional terhadap petani yang dipilih menggunakan teknik systematic random sampling. Responden memiliki usia rata-rata 54,97 ± 10,50  tahun dengan rentang usia antara 25 hingga 75 tahun. Sebanyak 75,56% responden adalah perempuan (n = 204), 24,44% adalah laki-laki (n = 66). Keuesioner terstruktur mengumpulkan data demografi, sampel darah untuk tingkat keamanan enzim kolinesterase, dan respon terhadap kuesioner World Health Organization Quality of Life Brief-Thai (WHOQOL-BREF-THAI). Data dianalisis menggunakan statistik deskriptif dan inferensial. Regresi linear berganda digunakan  untuk mengidentifikasi faktor-faktor yang terkait dengan skor WHOQOL-BREF-THAI, menyajikan adjusted mean differences, 95% confidence intervals (95% CI) , dan nilai p. Penelitian mengungkapkan bahwa rerata skor WHOQOL-BREF-THAI adalah 89,97 ± 10,34. Faktor-faktor yang berhubungan dengan skor ini antara lain jenis kelamin (laki-laki: 3,06; p = 0,032), luas lahan pertanian 10 Rai (1600 m2) ke atas (2,55; p = 0,039), frekuensi tes darah kolinesterase (1 kali: 3,01; tidak pernah: 3,40; p = 0,039; referensi: 2 kali atau lebih), dan tingkat keamanan enzim kolinesterase darah (tidak aman: 1,69; p = 0,037). Temuan ini menyoroti perlunya intervensi untuk mengurangi faktor-faktor risiko, khususnya di kalangan petani dengan tingkat enzim kolinesterase yang tidak aman, guna meningkatkan kualitas hidup pada populasi ini.Kata Kunci: kualitas hidup, petani, tingkat keamanan enzim kolinesterase